PERANAN KOMUNIKASI POLITIK PARTAI KEADILAN SEJAHTERA DALAM MEMPERTAHANKAN KEPERCAYAAN PUBLIK DI DAERAH PILIHAN III KOTA MEDAN - H. Jumadi; Irene Silviani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at analyzing how the role of political communication in maintaining public confidence in the Prosperous Justice Party (Partai Keadilan Sejahtera) Constituency III Medan City. The research method used in this study is qualitative research. The results show that the role of political communication in maintaining trust in the Prosperous Justice Party (Partai Keadilan Sejahtera) Constituency III Medan City was going well where as a political commander was able to convey his political messages through the party and was able to be carried out by the PKS by running well by invites the public to dialogue and adjust with the community's educational background and give the contents of the message clearly and in detail so as to be able to arouse attention arousing interest and interest so as to have a strong willingness to accept the decision of the message. Besides that, in delivering messages to the PKS community, they directly approached religious leaders in District III of Medan City